Demokrasi, Penegakan Hukum dan Politik Identitas di Indonesia - Dwi Ardiyanti; Anastasia Meilin Gita Permata Laia; M. Hafiz Nabiyyin (Department of Political Science - Universitas Sains Al-Qur’an, 2019)
The freedom of speech in Indonesia is one of characteristics of the well-runned democracy. Every citizen from any race, tribe, and religion is free to deliver their idea. This research focuses on the law enforcement especially to minority of Chinese tribe and the use of politics of identity in case of Meiliana in 2016. This research aims to explore and analyze the phenomenon of weakness in law enforcement especially for minority tribes in Indonesia as a democratic country. The method used in this research is literature research using qualitative data obtained from secondary resources such as books, journals, articles, and interviews posted in official websites. Moreover, the research strives to analyze some concepts and theory of politics of identity, and democracy.